COVID-19's effects on Paralympians - Cabador, J.; Mendoza, M. (2021)
The present study was conducted through the Adaptive Athletics at University of Houston (AAUH) Lab program, which is dedicated to studying the unique social and economic challenges and disparities people with disabilities face. Involvement in elite sports and athletic identity development has the potential to help people with disabilities combat social marginalization and enhance their well-being. For elite athletes with disabilities, the Paralympics are the premier stage and sporting event representing the greatest chance for single-source income for most Paralympic athletes in the U.S. With the one-year postponement of the Tokyo 2020 Paralympic Games due to the pandemic, Paralympic hopefuls are facing an entirely new set of challenges. The purpose of this study was to investigate COVID-19`s physical and mental impacts on Paralympic athletes` lives. This involved in-depth semistructured interviews conducted with 29 Paralympians and Paralympic hopefuls. It was observed that para-athletes were physically challenged by an overall decrease in sport participation, through less structured training and lack of training facility access. Due to this long period of reduced training intensity, para-athletes` mental health suffered severely resulting in negative feelings of uncertainty, anxiety, and depression. Outside of sport, para-athletes were found to be impacted as well. Because these athletes` lives are often shaped around sport, they faced challenges in their social interactions and future life plans. These finds are consistent with prior research on sport disruptions, however, previous studies have focused on elite able-body athletes` experiences. This study adds to this body of literature as it discusses the various challenges elite athletes with disabilities face through sport disruptions and the COVID-19 pandemic.